Cuban dental scientific production in the Web of Science: bibliometric analysis of the period 2007-2016 - Ibraín Enrique Corrales-Reyes; Alberto Juan Dorta-Contreras (Editorial Ciencias Médicas, 2018)
Introduction: Dental research in Cuba has had important progress. That's why, a bibliometric analysis would indicate the tendency that it takes. Objective: To describe the Cuban dental scientific production indexed in the Web of Science in the period 2007-2016. Methods : An observational, descriptive and cross-sectional study was performed through bibliometric analysis. The following variables were studied: amount of articles, citations, self-citations, typologies, topics, categories, Cuban institutions, provinces, language, year of publication, countries, number of authors per article, kinds of authorship, annual index of collaboration, kinds of collaboration, H index, annual growth rate, journals, impact factor, quartile and publications of high quality. Results: 57 articles (56 originals and one abstract) were published, which have an H index of 12 and have received 457 citations (96 self-citations) with an average of 8.02 and 50.78 citations per article and per year, respectively. The growth rate and the index of collaboration had a yearly average value of 45.79 % and 5.39 %, respectively. High quality articles (n= 49; 85,96 %) predominated, related with implantology (n= 47; 82,46 %) published in the first quartile Journal Oral Clinical Implants Research (n= 44; 77,19 %), as well as the international collaboration with Italy, Brazil, and China. The most cited article had an annual average of citations of 6.50, while the most productive researcher was Daniele Botticelli, with 47 articles and 369 citations, with an H index of 11. Conclusions: Cuban dental scientific production, as well as its impact in terms of citation, shows a tendency of irregular growth characterized by international high collaboration.